Growth Dynamics and Physiological Effects of Lead (Pb) Stress on Wheat (Triticum aestivum L.) - Huzaifa Ahmed Khan; Masood Ahmed khan; Dr Muhammad Ibrahim; Bhaveesh Chander; Muhammad Ahmad Sarwar; Muhammad Asif Khan; Muhammad Usama; Zubaida Hina; Mohammad Ashfaq; Sheraz Hussain, (Dialogue Social Science Review (DSSR), 2025)
A pot experiment was carried out to investigate how Lead (Pb), a harmful heavy metal, affects the growth and development of two wheat varieties: Chakwal-97 and Sehar-2006. The plants were exposed to three different levels of lead contamination in water: 0 parts per million (ppm), 40 ppm, and 60 ppm. The results showed that Lead (Pb) stress caused a reduction in several growth parameters, such as the length of shoots and roots, the fresh and dry weights of shoots, and the number of tillers per plant. The study also found that Lead (Pb) stress reduced the amount of important photosynthetic pigments, including chlorophyll-a (chl a) and chlorophyll-b (chl b), which are necessary for plants to make food through photosynthesis. However, the carotene content in the plants increased under Lead stress. In addition, essential ions like sodium (Na⁺) and potassium (K⁺), which play important roles in plant growth, were also decreased by Lead exposure.